Effect of yttrium addition timing on inclusion evolution and grain growth behavior in spring steel 55SiCr - Shuai Ma; Yang Li; Zhouhua Jiang; Meng Sun; Yunqie Mao; Yanshuo Ma; Yucheng Wang; Tianci Li; Yunfei Niedeng; Rui Yang; Hang Liu (Journal of Materials Research and Technology)
The effects of different yttrium addition timing on inclusion evolution and austenite grain growth behavior of spring steel 55SiCr were investigated. The results show that the addition of yttrium in the early stage of smelting is beneficial to the deoxidation of molten steel, but basically no desulfurization effect. The inclusions were partially modified from SiO2–Al2O3–MgO into Y2O3–SiO2–Al2O3, which have no effects on refinement of austenite grain. However, the addition of yttrium at the later stage of smelting can simultaneously achieve the effects of deoxidization and desulfurization, and the yield of yttrium reaches to 34.6% from 12.0%. Meanwhile, the inclusions were completely modified into Y2O2S and YS, and the inclusions achieved fine dispersion distribution, and the micrograin size grade of austenite grains was increased from 4.79 to 6.09. The calculation of Gibbs free energy of inclusion formation shows that the inclusions generated with the oxygen content from high to low are Y2O3→Y2O2S→YS when yttrium is added to spring steel. In this study, it is recommended to add yttrium in the later smelting stage, which is beneficial to improve the yield of yttrium, deoxidation and desulfurization of molten steel, modification of inclusions and grain refinement.